Neuroendocrine Carcinoma as an Independent Prognostic Factor for Patients With Prostate Cancer: A Population-Based Study - Yao, Jiping; Liu, Yanning; Liang, Xue; Shao, Jiajia; Zhang, Yina; Yang, Jing; Zheng, Min (Frontiers in Endocrinology, 2021)
Background: Neuroendocrine carcinoma is a highly malignant variation of prostate adenocarcinoma. We aimed to investigate the prognostic value of neuroendocrine carcinoma in prostate cancer. Methods: A total of 530336 patients of prostate cancer, including neuroendocrine carcinoma and adenocarcinoma from 2004 to 2018 were obtained from the national Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching (PSM), multivariable Cox proportional hazard model, Kaplan‐Meier method and subgroup analysis were performed in our study. Results: Neuroendocrine prostate cancer (NEPC) patients were inclined to be older at diagnosis (29.5% vs. 16.3%, P< 0.001) and had higher rates of muscle invasive disease (31.1% vs. 9.2%, P < 0.001), lymph node metastasis (31.1% vs. 2.2%, P < 0.001), and distal metastasis (45.4% vs. 3.6%, P < 0.001) compared with prostate adenocarcinoma patients. However, the proportion of neuroendocrine carcinoma patients with prostate‐specific antigen (PSA) levels higher than 4.0 ng/mL was significantly less than adenocarcinoma patients (43.7% vs. 72.9%, P<0.001). Neuroendocrine carcinoma patients had a lower rate of receiving surgery treatment (27.4% vs. 43.9%, P<0.001), but they had an obviously higher rate of receiving chemotherapy (63.1% vs. 1.0%, P<0.001). A Cox regression analysis demonstrated that the neuroendocrine carcinoma patients faced a remarkably higher risk of OS (HR = 2.78, 95% CI = 2.34–3.31, P < 0.001) and CSS (HR = 3.07, 95% CI = 2.55–3.71, P < 0.001) compared with adenocarcinoma patients after PSM. Subgroup analyses further suggested that NEPC patients obtained significantly poorer prognosis across nearly all subgroups. No significant interactions were found for potential covariates in both OS and CSS. Conclusion: The prognosis of neuroendocrine carcinoma was worse than that of adenocarcinoma among patients with prostate cancer, even after adjustment for demographic and clinicopathological characteristics by PSM. The histological subtype of neuroendocrine carcinoma is an independent prognostic factor for patients with prostate cancer.